Electroswitchable noble-metal-free catalysis for molecular solar thermal systems - Franz, Evanie; Fickenscher, Georg; Schulze, Erik J.; Krappmann, Daniel; Weidlich, Anna; Luchs, Tobias; Dreuw, Andreas; Hirsch, Andreas; Brummel, Olaf; Libuda, Jörg (ACS energy letters, 2025)
Molecular solar thermal (MOST) systems convert solar energy into chemical energy via a simple unimolecular reaction, enabling efficient energy storage. However, controlling the energy release remains a challenge. Here, we present an electroswitchable, noble-metal-free hybrid catalyst that enables energy release with high activity and selectivity. The MOST system is p-methoxyphenyl-ethyl ester-norbornadiene (mPENBD), which is photoconverted to its energy-rich quadricyclane isomer (mPEQC). A CoII porphyrin derivative, anchored as a self-assembled monolayer (SAM) on an atomically defined Co3O4(111) electrode, catalyzes the back-conversion of mPEQC to mPENBD with exceptional selectivity. Over 100 cycles, no side products were detected, and only minimal deactivation occurred. Most importantly, catalytic activity can be switched on and off via electrode potential due to the reversible conversion between an active CoII porphyrin SAM and an inactive CoI porphyrin SAM. This electroswitchable catalyst enables precise control of energy release in MOST-based solar energy storage systems.